KEEFEKTIFAN HERBISIDA IPA-GLIFOSAT (480 g/l) DALAM MENGENDALIKAN GULMA PADA BUDIDAYA KELAPA SAWIT TBM - Haryanus Ugot; Edy Syahputra; Rahmidayani Rahmidayani (Fakultas Pertanian Universitas Tanjungpura, 2022)
The objective of this study was to evaluate the herbicide effectiveness of IPA-Glyphosate (480 g/l) in control the common weeds on immature oil palm plantation. This study was performed in oil palm plantation at Rasau Jaya, Kubu Raya Regency, Kalimantan Barat Province. Vegetation analysis was conducted by using the square methods. Herbicide application carried out by a spraying method. Experiment arranged by randomized block design with 6 treatments and 4 replications. The results showed at 12 weeks after application the average density of weeds covering is 2,4-40%. The IPA- Glyphosate herbicide (480 g/l) with dose 5 l/ha effective suppressed the growth kinds of weeds up to 12 weeks after application and didn’t cause phytotoxicity in oil palm plantation.